In vitro anti-yeast activity, kinetics and mechanism of action of essential oils from two cameroonian medicinal plants - Flore Tatiana Kemegni Tchinang; Florentine Marie-Chantal Ndoyé Foé; Rodrigue Keumoe; Elisabeth Menkem Zeuko'o; Fabrice Boyom Fekam; François-Xavier Etoa (BMC, 2023)
Abstract Background Treatment of Candida infections have become increasingly difficult due to antifungal drug resistance, which has drawn attention toward the search for innovative and effective drugs. This study aimed to assess the activity of essential oils (EOs) from Pentadiplandra brazzeana Baillon (PB) root and Drypetes gossweileri S. Moore (DG) stem bark against Candida albicans and Candida parapsilopsis strains, and determine their antifungal mechanism when tested alone or combined. Methods The anticandidal activity of the EOs using the checkerboard format was assessed using the broth micro-dilution technique. The checkerboard microtiter test was performed to evaluate the interaction of the EOs. The in vitro pharmacodynamics of the EOs alone or combined, using time-kill assays, following the chequerboard technique were evaluated. The anticandidal mode of action of these EOs, combined or not, was investigated using the sorbitol protection assay, and the ergosterol binding assay. Differences (p < 0.05) between the experimental and the control groups were evaluated using one way analysis of variance (ANOVA) followed by Tukey's test for multiple comparisons. Results Essential oils (EOs) from Drypetes gossweileri (DG) stem bark showed activity with MIC value of 62.5 µg/mL against Candida albicans and Candida parapsilopsis, whereas EOs from Pentadiplandra brazzeana (PB) root exhibited MICs of 125 µg/mL and 250 µg/mL against the respective yeasts. The EOs were fungicidal with synergism on C. parapsilopsis and additivity on C. albicans, with 2 to 64-fold drop in MIC values. The MIC combination of 31.25/7.81 µg/mL and 1.95/31.25 µg/mL (DG/PB EOs) required 20 and 18 h of exposure, respectively to effectively kill 99.9% of the inoculum. This fungicidal effect was accompanied by alteration of the cell walls and membranes of yeasts. Conclusion The potency of the EOs combinations indicates further directions in their investigation as potential anticandidal agents.